Phytochemical Screening And Sun Protection Factor (Spf) Evaluation Of Butterfly Pea Flower (Clitoria Ternatea L.) Extract Lip Tint Product - Ramayani, Septiana Laksmi (Media Farmasi Indonesia, 2024)
A lip tint is a cosmetic preparation that colors lips while shielding them from UV light and free radical damage. The butterfly pea blossom is one plant that possesses sunscreen properties and can be used as a natural dye. The purpose of this study is to ascertain how the concentration of butterfly pea flower extract affects the SPF activity of lip tint products containing this extract. This study's design is entirely random, making it an experimental investigation. The in vitro SPF test results using Uv-Vis spectrophotometry show that at a concentration of 5%, 1.618162 SPF falls into the less group; at a concentration of 10%, 4.770857 SPF falls into the medium category; and at a concentration of 15%, 6.1224069 SPF falls into the extra category. The SPF value of lip tint preparations is influenced by the varied concentrations of butterfly pea flower extract, as indicated by the statistical analysis results, which indicate significant variations between the three concentrations (p<0.05).